SMEs in Supply Chains in Industry 4.0: A Question of Security and Risk - Marcel Rolf PFEIFER (Communications of International Proceedings, 2021)
Competing supply chains are the core in several industries. These supply chains are multinational and include companies of all sizes. SMEs account for more than 95% of the global manufacturing volume. Being part of supply chains, they also have a share in the supply chain’s risk management. Being believed to be the weakest members of supply chains, they impose a security risk for the whole supply chain. Studies on various risks came to the conclusion that SMEs are not able to cover the risks as large enterprises would be able to do it. In particular IT and data security is a field with no tangible return that is believed to be neglected by these enterprises. However, SMEs’ perceptions indicate that they assume themselves to be well-prepared, being equipped with above-average safety measures. The reality of IT security threats was confirmed by studies that assume the rate of already-attacked enterprises of all sizes and industries to be above 50%. Risk-mitigation strategies of downstream customers in the supply chains may backfire, as risks are able to spread through the supply chain. Vulnerable IT and data in SMEs may result in vulnerable IT and data also in larger enterprises. In order to achieve a supply chain resilience in the age of industry 4.0 and smart manufacturing, new technologies have to be used. A promising approach are blockchain technologies known from cryptocurrencies. Suggested to be resilient, traceable, anonymous, and secure, these technologies might enhance the IT security level of whole supply chains, including SMEs.
Keywords: SME; Supply Chain; Security; Risk; Industry 4.0; IT security